Exploring the Effectiveness of Psychological Health Education for College Students under the Background of Course Ideology and Politics - Chen, Renjun (Transactions on Social Science, Education and Humanities Research, 2024)
Due to social progress and technological development, China is entering a period of diverse cultural development. However, this diverse cultural development has also had some negative impacts, such as the worship of materialism and hedonism. College students are young, have limited social experience, and have weak self-restraint abilities, all of which can lead to an imbalance in their mentality and loss of thought. To better promote their mental health growth and further improve the quality of talent cultivation, we should strengthen our concepts, improve teaching methods, and integrate ideological and political education into the curriculum in mental health. In this way, we can integrate and interact with both. This article aims to explore how universities can closely link mental health with college students, and how to improve their psychology through this approach, making it more targeted in practical work.